2011
DOI: 10.1016/j.imlet.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

NSOM/QD-based fluorescence–topographic image fusion directly reveals nano-spatial peak–valley polarities of CD69 and CD71 activation molecules on cell-membrane fluctuations during T-cell activation

Abstract: Nano-spatial distribution of cell surface molecules on cell membrane fluctuations during T-cell activation has not been reported. In this study, we innovated application of near-field scanning optical microscopy (NSOM)/quantum dots (QD)-based nanotechnology through three-dimensional image fusion algorithm to merge the simultaneously-obtained dual-color fluorescence information and three-dimensional topography. This novel imaging system made it possible to visualize nano-spatial distribution and organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…As such, NSOM used in conjunction with QDs is the best technique by which the distribution of membrane receptors can be measured at the nanometer scale[30][31][32][33][34][35][36]. In this study, our results indicate that VEGF can induce directed migration of MSCs through the formation of (Focal Adhesion Kinase) FAK and cytoskeletal rearrangements.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…As such, NSOM used in conjunction with QDs is the best technique by which the distribution of membrane receptors can be measured at the nanometer scale[30][31][32][33][34][35][36]. In this study, our results indicate that VEGF can induce directed migration of MSCs through the formation of (Focal Adhesion Kinase) FAK and cytoskeletal rearrangements.…”
mentioning
confidence: 58%
“…Some studies suggest that CD44 plays a key role in cytoskeletal rearrangement [27], takes part in a CD44-Src-integrin signaling axis in lipid rafts [28], and most importantly, CD44 can be a co-receptor of VEGFR-2 [29]. [30]. Stimulated emission depletion (STED) and photoactivatable localization microscopy (PALM) lack simultaneous topographic information [31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently innovated the use of near-field scanning optical microscopy (NSOM) [ 19 , 20 ] and quantum dots (QD) based nanotechnology through dipole-polarization and dual-color to visualize nanoscale distribution and organization of antigen-specific TCR/CD3, coreceptor CD4, CD8, and nanospatial relationship between TCR/CD3 and CD4 or CD8 in sustained activation of primary T-cells [ 21 , 22 ]. In the current study, we intend to directly visualize nanoscale nanospatial relationship between TCR/CD3 and GM1 before and after T-cells activation, moreover to detect whether GM1 clustering or TCR/CD3 nanodomains are required for PKC θ signaling cascades and T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include flow cytometry (also known as fluorescence-activated cell sorting), [14][15][16][17] electron microscopy (EM), [18][19][20] and so-called super-resolution microscopy. [21][22][23][24] For example, scanning EM (SEM) and transmission EM (TEM) are common methods for imaging NP uptake in vitro and ex vivo. Gupta et al 25 and Gupta and Gupta 26 showed the accumulation of SPIONs at the cell surface by SEM and the location of SPIONs inside single human fibroblasts by TEM.…”
Section: Introductionmentioning
confidence: 99%